"Avoidable" mortality and health services: a review of aggregate data studies. Issue 2 (June 1990) - Mackenbach, J P; Bouvier-Colle, M H; Jougla, E
Abstract : STUDY OBJECTIVE–The aim of the study was to review published work reporting mortality from conditions amenable to medical intervention and compare the methods used and the results obtained. SOURCE MATERIAL–Two types of analysis were examined: (1) analyses of time trends, relating decline in mortality from amenable conditions to improvements in medical care (3 papers); (2) analyses of geographical variation, either between or within countries, in which mortality was related to the availability of health care resources and to other factors (8 papers). RESULTS–Time-trend studies have in general shown that mortality from amenable causes has declined faster over the past decades than most other causes of death. Studies of geographical variation have shown that mortality from amenable causes is consistently associated with socioeconomic factors, and that the association with the provision of health care resources is rather weak and inconsistent. CONCLUSIONS–(1) The low levels of mortality from amenable causes which presently prevail in industrialised countries are likely to reflect, at least in part, the increased effectiveness of health services; (2) geographical variation in mortality from amenable causes has not yet been shown to reflect differences in effectiveness of health services; and (3) if geographical variation in avoidable mortality does reflect such differences, they must arise from circumstances other than the level of supply, for example from more specific aspects of health care delivery, and are probably closely related to socioeconomic circumstances. In depth studies at the individual level are now more likely to produce information about factors limiting the effectiveness of health services than further studies of aggregate data.